2017
DOI: 10.1002/ejoc.201700395
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Approach to Pinguisane Sesquiterpenes: Total Synthesis of (–)‐Pinguisenol and (–)‐Isonaviculol

Abstract: A short and efficient enantioselective approach to pinguisane‐type sesquiterpenes has been developed starting from a Hajos–Parrish‐type ketone. This led to the first total syntheses of isonaviculol (10 steps, 6.6 % overall yield) and natural pinguisenol (9 steps, 12 % overall yield). The key reactions were regioselective thioketal protection, stereoselective cyclopropanation using Furukawa's protocol, diastereoselective hydrogenation of an olefin using a Thalesnano H‐Cube Pro flow reactor, Li/liquid NH3 mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…32–35 Finally, removal of the TBDPS groups of 26 and 27 using tetra- n -butylammonium fluoride (TBAF) furnished alcohols 4 and 28 quantitatively. 36,37 The analytical data of 1 H NMR, 13 C NMR, HRMS and IR of 4 were consistent with those of natural vetiverianine A ( 1 ). 4 However, [ α ] D of 4 was positive, whereas that of 1 was negative, and thus, they exhibited opposing absolute configurations.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…32–35 Finally, removal of the TBDPS groups of 26 and 27 using tetra- n -butylammonium fluoride (TBAF) furnished alcohols 4 and 28 quantitatively. 36,37 The analytical data of 1 H NMR, 13 C NMR, HRMS and IR of 4 were consistent with those of natural vetiverianine A ( 1 ). 4 However, [ α ] D of 4 was positive, whereas that of 1 was negative, and thus, they exhibited opposing absolute configurations.…”
Section: Resultssupporting
confidence: 67%
“…[32][33][34][35] Finally, removal of the TBDPS groups of 26 and 27 using tetra-n-butylammonium fluoride (TBAF) furnished alcohols 4 and 28 quantitatively. 36,37 The analytical data Scheme 1 Retrosynthetic analysis of vetiverianine A (1).…”
Section: Resultsmentioning
confidence: 99%
“…Yadav and coworkers reported a short and efficient enantioselective approach to pinguisane-type sesquiterpenes, and among others to the natural (-)-pinguisenol, from a Hajos-Parrish-type ketone (Scheme 7). The key reactions were regioselective thioketal protection, stereoselective cyclopropanation using Furukawa's protocol, diastereoselective hydrogenation of an olefin using a Thalesnano H-Cube Pro flow reactor, and Li/liquid NH3 mediated cyclopropane reduction (Yadav et al, 2017). A year later, the same group of authors reported the stereoselective total syntheses of pinguisane-type of sesquiterpenoids using a chiral building block derived from (R)-pulegone (Yadav et al, 2018).…”
Section: Total Synthesis Of Pinguisane-type Terpenoidsmentioning
confidence: 99%